2023
DOI: 10.1136/jnnp-2022-330203
|View full text |Cite
|
Sign up to set email alerts
|

Networks of microstructural damage predict disability in multiple sclerosis

Abstract: BackgroundNetwork-based measures are emerging MRI markers in multiple sclerosis (MS). We aimed to identify networks of white (WM) and grey matter (GM) damage that predict disability progression and cognitive worsening using data-driven methods.MethodsWe analysed data from 1836 participants with different MS phenotypes (843 in a discovery cohort and 842 in a replication cohort). We calculated standardised T1-weighted/T2-weighted (sT1w/T2w) ratio maps in brain GM and WM, and applied spatial independent component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Colato et al recently identified grey and white matter networks of microstructural damage assessed using the sT1w/T2w ratio in patients with multiple sclerosis. 49 Interestingly, they also identified an independent component (WM-IC6) that closely matches the damage pattern in our patients with NMDAR encephalitis. This could potentially indicate that this white matter network covers a specifically vulnerable brain region, or a brain region where multiple sclerosis and NMDAR encephalitis share (downstream) pathophysiological mechanisms.…”
Section: Neuro-inflammationsupporting
confidence: 72%
See 1 more Smart Citation
“…Colato et al recently identified grey and white matter networks of microstructural damage assessed using the sT1w/T2w ratio in patients with multiple sclerosis. 49 Interestingly, they also identified an independent component (WM-IC6) that closely matches the damage pattern in our patients with NMDAR encephalitis. This could potentially indicate that this white matter network covers a specifically vulnerable brain region, or a brain region where multiple sclerosis and NMDAR encephalitis share (downstream) pathophysiological mechanisms.…”
Section: Neuro-inflammationsupporting
confidence: 72%
“…47 Moreover, the major SLF component terminates in the dorsolateral prefrontal cortex, a brain region central to working memory that also promotes long-term memory formation. 48 Recent studies have demonstrated that cerebral white matter can also be analysed from a network perspective, both as a structural network 49 and as a functional connectivity network. 42 To estimate the functional implications of the observed white matter changes, we visually assessed overlap with the white matter functional atlas developed by Peer and colleagues.…”
Section: Neuro-inflammationmentioning
confidence: 99%
“…Disability worsening as measured by the EDSS was defined if an increase of the EDSS confirmed at least 3 months after the first documentation occurred during the study follow-up (EDSS increase of ≥ 1.5 if the baseline EDSS was 0, increase of ≥ 1.0 if the baseline EDSS was between 1.0 and 5.0). We defined worsening of the SDMT if a reduction of at least 4 points occurred (confirmed in a second follow-up visit) ( 13 ) and worsening of the T25W and 9HPT if an ≥ 20% increase in test times were recognized (confirmed in a second follow-up visit) ( 14 ). We excluded patients with any relevant eye disease possibly affecting the integrity of the retina and a refractory errors > 6 dioptres.…”
Section: Methodsmentioning
confidence: 99%